Valuing Ecotourism of a Recreational Site in Ciamis District of West Java, Indonesia - Saptutyningsih, Endah; Selviana, Rini (JEJAK: Jurnal Ekonomi dan Kebijakan, 2017)
Ecotourism, as an alternative tourism, involves visiting natural areas in order to learn, to study or to carry out activities environmentally friendly, that is a tourism based on the nature experience which enables the economic and social development of local communities. Ecotourism encourages rural economics and provides benefits to income and employment generation. It is considered as an alternative for enhancing rural lifestyle and for leading positive changes in the distribution of income. One of the area which has ecotourism site in Indonesia is Karangkamulyan site, Ciamis District of West Java. There is a tourist attraction that not only offers natural beauty, history and cool atmosphere, it also serves as a place of education and research on the history in the field of archeology. This attraction should receive special attention from the local government so that the tourists and local people also get the benefits. Ecotourism can be classified as possessing public goods-type characteristics, and as such, welfare benefit estimates must utilize non-market valuation techniques. This study employs the travel cost method and contingent valuation method. Travel cost and contingent valuation methods are applied to the problem of estimating the potential consumer surplus available to tourists from ecotourism in Ciamis. The results are compared with contingent valuation analysis of willingness-to-pay of tourists in their current trip to ecotourism sites of Ciamis. The result of travel cost method indicates that touristsâ average travel cost is estimated at no more than one hundred thousand rupiahs. The contingent valuation method concludes that the touristsâ average willingness to pay in their trip to ecotourism sites of Ciamis is are about IDR 6,800 in average.Â